The chocolate jewel case : [large type] - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2007)
In her rare free time, newlywed Lee McKinney Woodyard works on TenHuis Chocolade's newest offerings, chocolate jewels. But soon the town of Warner Pier has its very own jewel heist, and then a body is found in the lake. Lee can't help but wonder if the crimes are related. Maybe if she digs up some dirt, she'll hit the mother lode.